Olfactory responses of Drosophila suzukii females to host plant volatiles. (16th January 2015) - Revadi, Santosh; Vitagliano, Silvia; Rossi Stacconi, Marco V.; Ramasamy, Sukanya; Mansourian, Suzan; Carlin, Silvia; Vrhovsek, Urska; Becher, Paul G.; Mazzoni, Valerio; Rota‐Stabelli, Omar; Angeli, Sergio; Dekker, Teun; et al.
Abstract Drosophila suzukii Matsumura, an endemic pest in southeast Asia, has invaded Europe and the U.S.A. Unlike most of its closely related sibling species, the serrated ovipositor of D. suzukii permits ovipositing in undamaged fresh fruits. In the present study, volatiles are identified from host plants that are potentially involved in D. suzukii host recognition and oviposition behaviour. It is shown that mated females are attracted to volatiles emitted from intact fruits. The antennally‐active suite of compounds released from the fresh fruits is identified by gas chromatography coupled with electroantennographic detection, as well as gas chromatography‐mass spectrometry. In olfactometer bioassays, mated females are significantly attracted to an electroantennographically active volatile, isoamyl acetate, when tested at 10 µg of synthetic compound in a rubber septa, which has a release rate comparable to that of fresh fruits. In addition, a genomic survey shows that D. suzukii not only possesses the full repertoire of genes encoding odorant receptors activated by isoamyl acetate in D. melanogaster, but also that one of the genes, OR67a, is represented by five duplicated copies. These results indicate that D. suzukii uses olfactory cues to select oviposition sites. The identification of volatiles emitted by host fruits that attract D. suzukii may aid in the development of a selective and efficient synthetic lure for monitoring this pest. As a close relative of Drosophila melanogaster, D. suzukii provides a unique opportunity for understanding the physiological mechanisms involved in the shift of this species from use of rotten to ripe fruits for oviposition.